Heterogeneous Impact of Land-Use on Climate Change: Study From a Spatial Perspective - Jia, Shuaishuai; Yang, Cunyi; Wang, Mengxin; Failler, Pierre (Frontiers in Environmental Science, 2022)
Studies have shown that land and climate interact in complex ways through multiple biophysical and biogeochemical feedbacks. In this interaction mechanism, the carbon fixation effect among different land-use types and objective conditions among different regions have significant gaps, leading to the heterogeneous impact of land-use on climate change. This study takes temperature change as the observation index to reflect climate change, and analyzes the process of land use type adjustment affecting vegetation cover and climate change. Based on the data of 214 countries from 1990 to 2018, this paper uses the spatial Durbin model with temperature lag to verify the heterogeneous impact of land-use on climate change in two dimensions of land-use type (Agriculture, forestry and their subdivision structure) and region (latitude and land-sea difference). The following conclusions are drawn: (1) The impact of different land-use types on climate change is heterogeneous. The impact of agricultural land on climate change is not significant, but the increase of the forest land proportion will help to restrain the rise of national temperature. (2) The impact of land-use on climate change has regional heterogeneity. There is heterogeneity in the impact on climate change among sample countries of different latitudes. The geographical differences make the mechanism of land-use affecting climate change between island countries and mainland countries also have heterogeneity, mainly in that island countries are not affected by the land-use structure adjustment of neighboring countries. (3) A country’s climate change is affected by both its own land-use structure and the land-use structure of neighboring countries, and the latter is more critical. The conclusions in this study provide helpful supplementary evidence for the importance of international climate cooperation and provide a reference for proposing international initiatives to address climate change or establishing an international convention to address climate change.